The prevalence of periodontal diseases in Portugal and correspondent digital awareness for the period 2004-2017: analysis of data from Global Burden of Disease and Google Trends - Machado, Vanessa; Botelho, João; Neves, João Albernaz; Proença, Luís; Delgado, Ana Sintra; Mendes, José João (SPEMD, 2020)
Objectives: The progression of periodontal diseases at the Portuguese national level and its public awareness are of great interest, mainly due to the high burden of periodontitis. We aimed to evaluate the progression of the prevalence of periodontal diseases in Portugal and correspondent public awareness, between 2004 and 2017, by using data from the Global Burden of Disease, the Portuguese Directorate-General of Health and Google® Trends. Methods: Portuguese national data of periodontal disease prevalence in the period 2004-2017 were searched in the Global Burden of Disease tools of the Institute for Health Metrics and Evaluation and the Portuguese Directorate-General of Health. For data on public awareness, the Google® Trends comparison tool was used to study the trends of the Portuguese words for “Periodontitis,” “Gingivitis,” “Gums” and “Periodontal disease.” Results: Overall, the prevalence of periodontitis increased slightly from 11.3% to 11.7%, according to the Global Burden of Disease. During 2004-2017, the Google® Trends search term “Gums” was the most relevant. It increased steadily over time while the search term “Periodontal disease” decreased, and these search trends were significantly correlated (ρ=–0.670; P=0.009). Additionally, Google® Trends search term “Gingivitis” was significantly negatively correlated (ρ=–0.537; P=0.048), over time, with Global Burden of Disease data. Portuguese netizens predominantly tend to search for non-medical terms like “Gums” over more scientific terms like “Gingivitis,” “Periodontitis” or “Periodontal disease.” Conclusions: Despite periodontal diseases in Portugal being continuously increasing and above the world average, Google® Trends data show an apparent oral medical illiteracy related to periodontal diseases in the Portuguese population. However, digital awareness of periodontal diseases increased over time.
Keywords: Global Burden of Disease; Google Trends; Medical illiteracy; Public awareness; Periodontal diseases; Periodontitis